1979
DOI: 10.1002/cne.901870202
|View full text |Cite
|
Sign up to set email alerts
|

Visual thalamocortical connections in sheep studied by means of the retrograde transport of Horseradish‐Peroxidase

Abstract: In order to study the visual thalamocortical connections in the sheep, horseradish peroxidase (0.3--0.5 microliter of a 30% solution) has been injected in the gyri marginalis, ectomarginalis medius pars medialis, ectomarginalis medius pars lateralis and ectosylvius caudalis. The results show that: (1) the dorsal lateral geniculate nucleus (LGNd) projects to the former three gyri. Dorsal parts of the LGNd project to caudal areas, whereas its ventral parts project to rostral areas of these gyri; medial parts of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

1980
1980
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 48 publications
1
13
0
Order By: Relevance
“…Instead, two studies in cat would establish that the cat (but not primate) LGd provided extensive input to VISp as well as multiple extrastriate visual areas (Glickstein et al, ; Wilson & Cragg, ). Initially, the cat extrastriate LGd projections were thought to be an exception compared to other mammals, but both positive (Benevento & Yoshida, ; Bullier & Kennedy, ; Coleman & Clerici, ; Dräger, ; Fries, ; Garey & Powell, ; Haight et al, ; Hall & Diamond, ; Hernández‐González et al, ; Holländer & Hälbig, ; Hubel, ; Hughes, ; Karamanlidis et al, ; Kennedy & Bullier, ; LeVay & Gilbert, ; Lysakowski et al, ; Niimi & Sprague, ; Raczkowski & Rosenquist, ; Ribak & Peters, ; Sanderson et al, ; Tanaka et al, ; Towns et al, ; Weber et al, ; Winfield et al, ; Wong‐Riley, ; Yukie & Iwai, ) and negative/absent (Benevento & Ebner, ; L. A. Benevento & Standage, ; Caviness & Frost, ; Coleman & Clerici, ; Coleman et al, ; Colwell, ; Diamond et al, ; Dräger, ; Dürsteler et al, ; Garey & Powell, ; Glendenning et al, ; Gould et al, ; Harting et al, ; Hubel & Wiesel, ; Kaas et al, ; Karamanlidis & Giolli, ; Peters & Saldanha, ; Robson & Hall, ) reports of LGd extrastriate projections in multiple species led to debate over the next several decades.…”
Section: Introductionmentioning
confidence: 99%
“…Instead, two studies in cat would establish that the cat (but not primate) LGd provided extensive input to VISp as well as multiple extrastriate visual areas (Glickstein et al, ; Wilson & Cragg, ). Initially, the cat extrastriate LGd projections were thought to be an exception compared to other mammals, but both positive (Benevento & Yoshida, ; Bullier & Kennedy, ; Coleman & Clerici, ; Dräger, ; Fries, ; Garey & Powell, ; Haight et al, ; Hall & Diamond, ; Hernández‐González et al, ; Holländer & Hälbig, ; Hubel, ; Hughes, ; Karamanlidis et al, ; Kennedy & Bullier, ; LeVay & Gilbert, ; Lysakowski et al, ; Niimi & Sprague, ; Raczkowski & Rosenquist, ; Ribak & Peters, ; Sanderson et al, ; Tanaka et al, ; Towns et al, ; Weber et al, ; Winfield et al, ; Wong‐Riley, ; Yukie & Iwai, ) and negative/absent (Benevento & Ebner, ; L. A. Benevento & Standage, ; Caviness & Frost, ; Coleman & Clerici, ; Coleman et al, ; Colwell, ; Diamond et al, ; Dräger, ; Dürsteler et al, ; Garey & Powell, ; Glendenning et al, ; Gould et al, ; Harting et al, ; Hubel & Wiesel, ; Kaas et al, ; Karamanlidis & Giolli, ; Peters & Saldanha, ; Robson & Hall, ) reports of LGd extrastriate projections in multiple species led to debate over the next several decades.…”
Section: Introductionmentioning
confidence: 99%
“…The visual area of the ovine cortex was identified based on the available stereotaxic atlases of the species (Richard, 1967; Vanderwolf and Cooley, 2002; Nitzsche et al ., 2015) and relevant literature (Rose, 1942; Clarke and Whitteridge, 1976; Clarke et al ., 1976; Karamanlidis et al ., 1979). The immunocytochemistry of the visual area in the sheep caudal cortex around the lateral sulcus identified largely different GABA‐ergic interneuron populations within the cortical thickness (Figure 4).…”
Section: Resultsmentioning
confidence: 99%
“…Our data suggest that contralateral connections are absent in the sheep, or perhaps very limited as in the cat (Olson and Graybiel, 1980). We also note that connections (seeding from the claustrum, Figure 5(f)) may reach peristriate areas such as V2, V3, or V4 that we did not map, because their precise location and topography has not been identified in the sheep, although tracing studies showed a quite wide visual territory (Karamanlidis et al ., 1979). The absence of contralateral projections could be of prime importance if confirmed by other studies, to rule out the role of the Cl in stereopsis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations